2015
DOI: 10.1002/cvde.201504330
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Oxycarbide Thin Films by Remote Microwave Hydrogen Plasma CVD Using a Tetramethyldisiloxane Precursor

Abstract: The effect of substrate temperature (TS) on the growth rate, chemical structure, surface morphology, density, refractive index, and optical absorption of a‐SiCO:H films is reported. The increase in TS from 30 °C to 350 °C involves the transformation of the film from polymeric, low‐density material to strongly cross‐linked, dense Si‐oxycarbide ceramics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…The results of our earlier study revealed that TMDSO forms by RP‐CVD a‐SiCO:H films of excellent morphological homogeneity and very promising properties. To extent the previous study we investigate the effect of substrate (or deposition) temperature ( T S ) on the kinetics of RP‐CVD, chemical structure, and surface morphology of a‐SiCO:H films, as well as their some important properties, such as: density, refractive index, optical absorption, optical bandgap, and photoluminescence. On the basis of structural data the hypothetical elementary reactions involved in film formation are proposed.…”
Section: Introductionmentioning
confidence: 82%
“…The results of our earlier study revealed that TMDSO forms by RP‐CVD a‐SiCO:H films of excellent morphological homogeneity and very promising properties. To extent the previous study we investigate the effect of substrate (or deposition) temperature ( T S ) on the kinetics of RP‐CVD, chemical structure, and surface morphology of a‐SiCO:H films, as well as their some important properties, such as: density, refractive index, optical absorption, optical bandgap, and photoluminescence. On the basis of structural data the hypothetical elementary reactions involved in film formation are proposed.…”
Section: Introductionmentioning
confidence: 82%
“…Recently, some stable Si–O–C materials have been synthesized containing the addition of a fourth element—hydrogen . One route involves chemical vapor deposition (CVD) or plasma‐enhanced CVD (PECVD) to make thin film SiOCH materials using various organosilane or alkoxysilane precursors in combination with strong or weak oxidizers such as O 2 , N 2 O, and CO 2 . Currently, the PECVD method has been widely adopted within the semiconductor industry for depositing amorphous SiOCH (a‐SiOCH) materials with values of dielectric permittivity that are substantially reduced relative to SiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“… Assignments H 2 O, SiOH CH 3 SiH Si(CH 3 ) x Si(CH 2 ) n Si, SiOSi Si 3 CH Samples Wavenumber (cm −1 ) TMS(5 min) 1634, 3445 1411, 2957 2120 794, 836, 1254 1031 686 TMS(20 min) 1632/3478 1410, 2959 2111 795, 838, 1256 1035 686 TMS + O 2 (5 min) 886, 1630, 3401 1409, 2963 799, 842, 1260 1037 697 Gaseous TMS 1428, 2963 1253 Ref. [37] [33] [38] [ 14 , 38 , 39 , 40 ] [ 26 , 38 , 41 ] [42] …”
Section: Resultsmentioning
confidence: 99%
“…The DDBD can cover a large surface area that make it possible for uniform coating over the surface, and consumes relatively low electric power compared to vacuum-based plasmas like rf and microwave plasmas. SiO x C y H z films deposited by a NTP method with their unique electronic, optoelectronic, chemical and wettability properties have been utilized in many application areas ranging from very large scale integration (VLSI) technology to hydrophobic coatings [ 25 , 26 ]. Tetramethylsilane (TMS) was chosen as the precursor because of its high chemical reactivity and vapor pressure (11.66 psi at 20 °C) compared to other monomers such as hexamethyldisiloxane.…”
Section: Introductionmentioning
confidence: 99%